Strategies for Overcoming Gender Bias in Islamic Religious Education at SMP Negeri 29 Bandar Lampung - Kamelia; Agus Pahrudin; Uswatun Hasanah (Universitas Islam Negeri Alauddin Makassar, 2025)
This research aims to analyze strategies for addressing gender bias in Islamic Religious Education (PAI) at SMP Negeri 29 Bandar Lampung. Using a qualitative approach, the study explores both teacher and school strategies in minimizing gender bias within the teaching and learning process. Data were collected through interviews, observation, documentation, and literature review to identify the forms of gender bias and how they are addressed. The findings show that gender bias mitigation strategies in PAI are divided into two main categories: teacher strategies and school strategies. Teacher strategies involve the implementation of collaborative learning, project-based learning (PBL), and reflective learning. Methods such as discussion, debate, and role playing are also applied. Furthermore, teachers serve as role models by using gender-inclusive language, being emotionally and socially sensitive to students, and creating a safe and supportive learning environment. Meanwhile, school-level strategies include teacher training, curriculum development with a gender perspective, and regular monitoring activities. These combined efforts contribute not only to improving the quality of interaction between teachers and students but also to building a more inclusive learning environment where both male and female students have equal opportunities to develop their potential without being limited by gender role stereotypes.